Decay constants of the pion and its excitations in holographic QCD - Ballon-Bayona, Alfonso [UNESP]; Krein, Gastão [UNESP]; Miller, Carlisson [UNESP] (American Physical Society (APS), 2015)
We investigate the leptonic decay constants of the pion and its excitations with a 5-d holographic model for quantum chromodynamics. We prove numerically that the leptonic decay constants of the excited states of the pion vanish in the chiral limit when chiral symmetry is dynamically broken. This nontrivial result is in agreement with a solid prediction of quantum chromodynamics and is based on a generalized Gell-Mann-Oakes-Renner relationship involving the decay constants and masses of the excited states of the pion. We also obtain an extended partially conserved axial-vector current relation that includes the fields of the excited states of the pion, a relation that was proposed long ago in the context of current algebra.